Increased Virulence of Bloodstream Over Peripheral Isolates of P. aeruginosa Identified Through Post-transcriptional Regulation of Virulence Factors - Hickey, Caitríona; Schaible, Bettina; Nguyen, Scott; Hurley, Daniel; Srikumar, Shabarinath; Fanning, Séamus; Brown, Eric; Crifo, Bianca; Matallanas, David; McClean, Siobhán; Taylor, Cormac T.; Schaffer, Kirsten (Frontiers in Cellular and Infection Microbiology, 2018)
The factors influencing the virulence of P. aeruginosa in the development of invasive infection remain poorly understood. Here, we investigated the role of the host microenvironment in shaping pathogen virulence and investigated the mechanisms involved. Comparing seven paired genetically indistinguishable clinical bloodstream and peripheral isolates of P. aeruginosa, we demonstrate that isolates derived from bloodstream infections are more virulent than their peripheral counterparts (p = 0.025). Bloodstream and peripheral isolates elicited similar NF-kB responses in a THP-1 monocyte NF-kappaB reporter cell line implicating similar immunogenicity. Proteomic analysis by mass spectrometry identified multiple virulence and virulence-related factors including LecA and RpoN in significantly greater abundance in the bacterial supernatant from the bloodstream isolate in comparison to that from the corresponding peripheral isolate. Investigation by qPCR revealed that control of expression of these virulence factors was not due to altered levels of transcription. Based on these data, we hypothesize a post-transcriptional mechanism of virulence regulation in P. aeruginosa bloodstream infections influenced by surrounding microenvironmental conditions.